THU0524B EXTRA-OCULAR MANIFESTATIONS OF CHILDREN WITH SARCOID-LIKE UVEITIS. (June 2019) - Shivpuri, Abhay; Kalms, Emily; Solebo, Ameenat Lola; Petrushkin, Harry; Thomas, Dhanes; Graham, Elizabeth; Edelsten, Clive; Compeyrot-Lacassagne, Sandrine
Abstract : Background: Paediatric sarcoidosis may represent a spectrum of disease. Early onset sarcoidosis & its genetically defined counterpart Blau syndrome associated with NOD2 mutations are characterized by fever, rash, arthritis and organomegaly. Later onset sarcoidosis has wider organ involvement including lungs, kidneys, lachrymal and extra-ocular glands. Both presentations may lead to long term complications due to end-stage organ damage. Although similar disease manifestations can be seen in adults and children, some entities are essentially pediatric at onset, namely Blau syndrome and most forms of immunodeficiency associated granulomatous diseases. Ocular sarcoidosis has a well described uveitis phenotype (1). We created a retrospective cohort of patients currently followed at GOSH with likely ocular manifestation of sarcoidosis (1) Objectives: To describe a retrospective cohort of children with sarcoid-like uveitis, To describe their extra-ocular manifestations at the time of the study, To describe their management Methods: retrospective case review of children currently followed at GOSH with a phenotype of ocular sarcoidosis with uveitis (ophthalmologist defn (5, 6)), or a diagnosis of idiopathic uveitis (anterior, posterior, intermediate or panuveitis) with raised ACE level at least once. We collected demographics and all extra-ocular involvement described in sarcoidosis Results: 52 patients. 27/52 males. Median age onset of uveitis 4.20 yrs (1.41-15.16). 30/52had onset <8 yrs. Median ACE 73 and mean ACE 77 at presentation (0-90U/L normal). Median max ACE79& mean max ACE 88.2 (14-420).NOD2 done in 12 patients: 6+, 6-. Only 4/6 patients Blau phenotype. Ethnicity: black 13, asian 10, caucasian 13, unknown 16/52. 49/52 patients had bilateral uveitis. Uveitis anterior 17/52, intermediate 5/52, posterior 2/52, panuveitis 25/52, unknown 1/52. ANA+15/47(32%). Extra-ocular (n=52): Lymphadenopathy : 15 (29%) clinically Liver : 16 (31%) - transaminitis 9, ultrasound(USS) abnormality (hepatomegaly, calcification, increased echogenicity) 5 & both abnormal USS & blood 2 Arthritis : 15 (29%) large joints of lower limbs & joints hands. Tenosynovitis 4 (7.7%) Renal : 15 (29%) (USS or Blood/urine tests – raised serum creatinine, raised urinary ca creat ratio, raised urinary NAG/RBP) — 4/15 on USS and 9/15 in blood/urine tests, 2/15 on both USS and blood/urine tests. Lungs : 7 (13.5%): 6 abnormal lung function test, 1abnormal CXR, lung function& CT chest - severe interstitial lung disease & presented- progressive shortness of breath. Skin: 10(19.2%), eczema-like/non-specific skin Parotid/glandular : 1 (1.9%) on USS Splenomegaly: 4 (7.7%) on USS Sensorineural hearing loss : 2 (3.8%) Medications to treat uveitis and/or extra-ocular manifestations were: Methotrexate 13 (25%), Methotrexate + Adalimumab 11 (21.2%), MMF 6 (11.5%), topical steroids 8 (15.4%), systemic steroids 2 (3.8%). 10 patients no medication Conclusion: Most of the sarcoid-like uveitis patients had at least one extra-ocular involvement. ACE does not appear to be a sensitive biomarker. Some patients (19.2%) have a mild phenotype and require no treatment. Our data demonstrate the importance of close monitoring for extra-ocular manifestations and highlight good clinical response to steroids, MTX, MMF and anti-TNF. Reference: [1] Acharya NR et al International Ocular Sarcoidosis Working Group. Distinguishing Features of Ocular Sarcoidosis in an International Cohort of Uveitis Patients. Ophthalmology. 2018 Jan;125(1):119-126. Disclosure of Interests: Abhay Shivpuri: None declared, Emily Kalms: None declared, Ameenat Lola Solebo: None declared, Harry Petrushkin: None declared, Dhanes Thomas: None declared, Elizabeth Graham: None declared, Clive Edelsten: None declared, Sandrine Compeyrot-Lacassagne Grant/research support from: Abbvie